Psychometric properties of the Chinese-version Behavioral Inhibition System/Behavioral Activation System Scales among stroke survivors with depressive symptoms - Dan Shi; Yuen Yu Chong; Lijuan Zhou; Ho Yu Cheng (International Journal of Nursing Sciences, 2025)
Objective: This study aimed to examine the reliability and validity of the Chinese version of the Behavioral Inhibition System/Behavioral Activation System (BIS/BAS) scales among stroke survivors. Methods: The cross-sectional study was conducted at four comprehensive hospitals in Taizhou, Jiangsu, China. A sample of 232 first-ever stroke survivors were recruited from June to August 2023. Validity was examined using face validity and construct validity, which used confirmatory factor analysis (CFA) and known-group analysis. Reliability was evaluated by internal consistency and test-retest reliability. Results: The BIS/BAS scales demonstrated satisfactory face validity. The findings of CFAs supported the original four-factor structure of BAS-reward, BAS-drive, BAS-fun seeking, and BIS with acceptable model fit indices. Discriminative validity, assessed via known-group analysis, indicated that stroke survivors with probable depression had significantly lower mean BAS-reward, BAS-drive, and BAS-fun seeking scores (P < 0.001) and a higher mean BIS score (P = 0.028) compared to those without probable depression. The internal consistency, measured by Cronbach’s α coefficients for the subscales, ranged from 0.669 to 0.964. Test-retest reliability, assessed using intra-class correlation coefficients, ranged from 0.61 to 0.93. Conclusions: The Chinese version of the BIS/BAS scales could be a reliable and valid instrument for measuring behavioral activation among stroke survivors.